TEACHERS’ CHALLENGES IN PROMOTING INTERCULTURAL AWARENESS IN SPEAKING SKILLS INSTRUCTION - Christie Urai Musa; Basikin (Universitas Muhammadiyah Makassar, 2026)
Intercultural awareness has become increasingly vital in English language training, particularly in speaking skills, as globalization needs successful communication across many cultural contexts. Despite its theoretical importance, many teachers still experience difficulties in integrating intercultural elements into classroom instruction. This study aims to investigate the lived experiences of Indonesian English teachers in promoting intercultural awareness within speaking education, focusing on the challenges they encounter and the strategies they employ to overcome them. The study is significant because it provides contextual insights into intercultural speaking instruction in Indonesian senior high schools, an area that remains underexplored in previous research. Using a qualitative phenomenological approach, data were collected through semi-structured interviews, classroom observations, and document analysis involving four English teachers at a private senior high school in Yogyakarta. The data were analyzed using thematic analysis to identify recurring themes related to teachers’ experiences. The findings revealed several challenges, including limited teacher confidence and intercultural knowledge, insufficient professional development, lack of culturally diverse teaching resources, curriculum constraints, student disengagement, and the persistence of stereotypes and misconceptions. Despite these challenges, teachers attempted to promote intercultural awareness through digital media, group discussions, peer interaction, and collaborative activities. This study contributes to the existing literature by demonstrating that challenges in intercultural speaking instruction are strongly influenced by structural and institutional conditions rather than solely by individual teacher limitations. In conclusion, intercultural awareness can be systematically developed through improved teacher preparation, continuous professional development, adequate resources, and stronger institutional and curricular support